Human Capital and Digital Adoption Driving Entrepreneurial Performance through Innovation Capability - Amna Manzoor (Journal of Advanced Research in Social Sciences and Humanities, 2026)
Aim: This study investigates how digital adoption and human capital influence entrepreneurial performance among Small and Medium-Sized Enterprises (SMEs) in China, with innovation capability as a mediating mechanism and environmental turbulence as a moderating factor. The research aims to provide a comprehensive understanding of how technology and intellectual resources translate into performance outcomes in rapidly changing market environments.Methodology: A quantitative, cross-sectional survey was conducted using data collected from 261 decision-makers of technology-intensive and manufacturing SMEs in China. Established and validated measurement scales were adapted from past research, and SmartPLS 4.0 was utilized to test the measurement and structural models. Mediation and moderation effects were examined through bootstrapping techniques.Findings: The results reveal that both digital adoption and human capital significantly enhance entrepreneurial performance. Innovation capability was found to mediate both relationships, confirming its critical role in transforming internal resources into strategic outcomes. Moreover, environmental turbulence negatively moderated the effect of digital adoption and human capital on innovation capability, indicating that high environmental uncertainty weakens resource effectiveness.Implications/Novel Contribution: This study offers an integrated theoretical contribution by combining the Resource-Based View, Dynamic Capability Theory, and Contingency Theory. Practically, it provides strategic guidance for SMEs to balance digital investments, talent development, and adaptive innovation strategies amid uncertain environments.